Clinical Characteristics and Survival Outcomes for Non-Small-Cell Lung Cancer Patients with Epidermal Growth Factor Receptor Double Mutations. (16th January 2018) - Peng, Min; Weng, Yi Ming; Liu, Hua Li; Yang, Gui Fang; Yao, Yi; Han, Guang; Song, Qi Bin
Abstract : Multiple randomized clinical trials have demonstrated that epidermal growth factor receptor (EGFR) exon 19 deletion (19Del) and exon 21 L858R mutation (L858R) are highly correlated with sensitivity to epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) treatment in non-small-cell lung cancer (NSCLC). A mutation in exon 20 (T790M) is reportedly associated with resistance to EGFR-TKIs. However, few studies have focused on patients harboring double mutations in these 3 mutation sites. In this retrospective study, forty-five patients (45/2546, 1.7%) harbored double mutations of 19Del, L858R, and T790M. Twenty-four patients with EGFR double mutations received EGFR-TKI therapy. Clinical characteristics of these patients, including the response to EGFR-TKIs and progression-free survival outcome for EGFR-TKI treatment (PFS-TKI), were analyzed. Patients with EGFR double mutations were more likely to be nonsmokers, have an Eastern Cooperative Oncology Group Performance Status (ECOG PS) of 0-1, have adenocarcinoma, and be at stage III-IV. The ORR, DCR, and median PFS-TKI in patients harboring EGFR double mutations were lower than in patients with a single EGFR-activating mutation. The differences in ORR and DCR were statistically insignificant between the 3 groups. Patients with double mutations of 19Del and T790M had longer PFS-TKIs than patients in the other 2 groups.